(untitled) (Archaeologia Adriatica, 2017)
The port basin of Roman Savudrija, once part of the ager of Tergeste colony, comprised a large number of port infrastructure facilities. Today, some of the port structures are submerged and some can be found in the soil profile on dry land. The remains of walls on the southern part of the coastline probably belonged to the superstructure of the first, lowest terrace of the port. Owing to the archaeological data obtained during the 2011-2014 excavations, we can date the construction and recreate the appearance of the coastline in Roman times. However, the evidence obtained so far touches upon the issue of the archaeological context of the Roman port of Savudrija in the hierarchy of the ports on the Istrian coast and its relationship with the nearby villas located along the coast and in the hinterland.